RKKY interaction between extended magnetic defect lines in graphene - Ferreira, Mauro; Power, Stephen (My University, 2014)
Of fundamental interest in the field of spintronics is the mechanism of indirect exchange coupling between magnetic impurities embedded in metallic hosts. A range of physical features, such as magnetotransport and overall magnetic moment formation, are predicated upon this magnetic coupling, often referred to as the Ruderman-Kittel-Kasuya-Yosida (RKKY) interaction. Recent theoretical studies on the RKKY in graphene have been motivated by possible spintronic applications of magnetically doped graphene systems. In this paper a combination of analytic and numerical techniques are used to examine the effects of defect dimensionality on such an interaction. We show, in a mathematically transparent manner, that moving from single magnetic impurities to extended lines of impurities effectively reduces the dimensionality of the system and increases the range of the interaction. This has important consequences for the spintronic application of magnetically-doped systems, and we illustrate this with a simple magnetoresistance device.
PUBLISHED
Keywords: spintronics; spintronics; Nanoscience & Materials; Magnetism and spin electronics; Nanotechnology; Physics